Parallel computation of viscous incompressible flows with heat transfer using second-order projection methods - Chong, Aik Fong. (2008)
In this study, second-order projection method is implementated in the solution of the three-dimensional viscous, incompressible Navier-Strokes equations, with the addition of the energy equation. In order to shorten the computation time, parallel computation is implemented.